2013
DOI: 10.1103/physrevlett.110.163203
|View full text |Cite
|
Sign up to set email alerts
|

Fast Ion Surface Energy Loss and Straggling in the Surface Wake Fields

Abstract: We have measured the stopping powers and straggling of fast, highly ionized atoms passing through thin bilayer targets made up of metals and insulators. We were surprised to find that the energy losses as well as the straggling depend on the ordering of the target and have small but significantly different values on bilayer reversal. We ascribe this newly found difference in energy loss to the surface energy loss field effect due to the differing surface wake fields as the beam exits the target in the two case… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Whereas, the distinction between the measurements through the K-REC peak and the empirical results discerns that the REC process is one of the important chargeexchange processes originating at the surface; the role of dynamic screening and wake effects may be vital. The processes at the exit surface of the foil may include the formation of excited projectile bound states as high as Rydberg states due to nonradiative electron capture and wake riding electron capture to circular Rydberg states [13,14] occurred because of finite surface wake field produced right at the exit surface [15,29]. The electrons, captured at such high-lying Rydberg states, are quite longlived and therefore can be detected with the electromagnetic techniques.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas, the distinction between the measurements through the K-REC peak and the empirical results discerns that the REC process is one of the important chargeexchange processes originating at the surface; the role of dynamic screening and wake effects may be vital. The processes at the exit surface of the foil may include the formation of excited projectile bound states as high as Rydberg states due to nonradiative electron capture and wake riding electron capture to circular Rydberg states [13,14] occurred because of finite surface wake field produced right at the exit surface [15,29]. The electrons, captured at such high-lying Rydberg states, are quite longlived and therefore can be detected with the electromagnetic techniques.…”
Section: Resultsmentioning
confidence: 99%
“…Several physical processes originating from the solid surfaces, for example, wake riding electron capture [13] leading to the formation of circular Rydberg states [14], electron capture in low-lying and high-lying states, etc., contribute in the dynamicity of the charge-changing processes. The excited states produced by any of the above processes can be further affected by the surface energy loss field (SELF) at the exit surface [15]. These charge-changing processes can be investigated through the distribution of charge state fractions (CSF) called charge state distribution (CSD) for both experiments and theories.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this fact was not known and mistakenly, CSD-O had been used in place of CSD-I [1] in studying inner shell ionization. Note that the innershell ionization of target atoms taking place inside the target, circular Rydberg state forming near the exit surface [2], ion energy-loss mostly happening inside the target and further modified in the exit surface [3] etc. demands the knowledge of CSD-I.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of the wake effect was also studied on solid surfaces, both in theoretical works [7,8] and in experiments [9,10], which demonstrated vicinage effects in the Coulomb explosion and energy loss of diatomic molecules grazingly scattered on crystal surfaces. In the more recent experiments, it was shown that the surface wake also plays a role in the energy loss and straggling of fast ions traversing a dielectric boundary [11] and that it affects the formation of circular Rydberg states in beam-foil experiments [12]. While the above studies were concerned with the wake due to electronic collective modes in solids and their surfaces, there were several studies addressing the role of the wake due to the excitation of the Fuchs-Kliewer (FK) or optical surface phonon modes in ion scattering from polar surfaces [13,14].…”
Section: Introductionmentioning
confidence: 99%